Innovation in the Management of Quality Indicators Through Dashboards: a Case Study - Teixeira, Létison Elias; Fagundes, Alexandre Borges; Augusto, Mário Ezequiel (Revista de Gestão e Secretariado, 2025)
THIS IS AN ARTICLE PUBLISHED BY Revista de Gestão e Secretariado (e-ISSN: 2178-9010) ON 2025-06-30, AVAILABLE ONLINE: https://doi.org/10.7769/gesec.v16i6.4964 Abstract Given the high level of market competitiveness, companies are increasingly required to offer high-quality products and services to their customers. To achieve this, the Quality Management area of a company requires clear indicators and reports that facilitate better decision-making. This is a common situation for many companies that use multiple data sources to build their reports, which feed their Quality Management Key Performance Indicators (KPIs). However, manual data handling and the lack of suitable tools for data analysis and visualization become problematic. This article introduces an innovative solution that combines Information Systems techniques and Quality Management concepts, demonstrating how informative dashboards can be created for publishing Quality Management performance indicators. Using this technology, routines can be optimized, redundant tasks eliminated, flexible analysis supported, and decision-making accuracy improved, making the production system more sustainable.
Keywords: Quality Management; KPIs; Innovation; Information Systems; Dashboards